Knowledge mapping of anaplastic thyroid cancer treatments: a bibliometric analysis (2000-2023) - Liu, Shiqiang; Yan, Xingmin; Yang, Yalong; Xia, Yun; Zhang, Panshi (Frontiers in Oncology, 2024)
Context ： Anaplastic thyroid cancer (ATC) is a relatively rare and extensively malignant kind of thyroid carcinoma. The poor prognosis and high mortality rate of ATC can be attributed to its invasive features and undifferentiated phenotype. At present, there is a lack of efficacious therapeutic options. In light of the elevated fatality rate, it is vital to possess a comprehensive comprehension of the scientific terrain pertaining to ATC. To gather the perspectives of different researchers about the topic of ATC treatment, we did a bibliometric network analysis, which offers a comprehensive view of the scholarly literature.A systematic search was conducted on the WoSCC database to identify publications pertaining to ATC treatment between the years 2000 and 2023.In this bibliometric investigation, the tools VOSviewers, CiteSpace, and the R package "bibliometrix" were employed to investigate the general attributes, developmental framework, and academic frontiers of the subject matter.Results: 1223 publications in total, written by 6937 scholars from 53 areas and 1402 institutions and published in 358 scholarly journals, were analyzed. There has been a gradual increase in the quantity of publications pertaining to ATC treatment. The United States and China emerged as the most prominent nations.